A quantitative analysis of the transition of fracture mechanisms of Ti6Al4V over a wide range of stress triaxiality and strain rate. (15th May 2020) - Wang, Bing; Xiao, Xinran; Astakhov, Viktor P.; Liu, Zhanqiang
Highlights: Fracture tests of Ti6Al4V were performed over a wide range of stress triaxiality and strain rate. The fracture mechanisms of Ti6Al4V were systematically studied at micro-scale. A quantitative criterion of fracture mechanism transition for Ti6Al4V was firstly proposed. The effects of stress state and strain rate on fracture mechanism of Ti6Al4V were revealed. Abstract: The material fracture behavior and associated mechanism is known to be affected by the stress state and strain rate. Using a recently developed rectangular hat-shaped specimen, the fracture behavior of Ti6Al4V was investigated with a stress triaxiality varying from −0.31 to 0.50 at strain rates ranging from quasi-static to 10 4 /s. The fracture mechanisms of Ti6Al4V under these conditions were studied at micro-scale through observations of cross-sectional microstructure and quantitative analysis of fracture surface morphology. It was found that λ, a parameter defining the percentage of equiaxed dimples on the fracture surface, shows a close correlation with the observed fracture mechanism. Therefore, a λ based criterion based has been introduced in this work to quantitatively describe the transition of fracture mechanisms. It was observed that the embrittlement of Ti6Al4V was promoted by a higher strain rate or a larger positive stress triaxiality, as expected. However, the stress triaxiality appeared to play a more dominant role. At sufficiently high negative or positive stress triaxiality values, the effect of strain rate on fracture mechanism became negligible.